Outbreak of Chagas disease in Brazil: Validation of a molecular diagnostic method - Costa-Oliveira, Cíntia Nascimento da; Paiva-Cavalcanti, Milena de; Barros, Michelle da Silva; Nakazawa, Mineo; Melo, Maria Gabriella Nunes de; Pessoa-e-Silva, Rômulo; Torres, Diego José Lira; Oliveira, Kamila Kássia dos Santos; Moreira, Leyllane Rafael; Morais, Rayana Carla Silva de; Goes, Tayná Correia de; Oliveira, Gênova Maria de Azevedo; et al. (Experimental parasitology, 2023)
Chagas disease (CD), caused by the protozoan Trypanosoma cruzi (T. cruzi), affects millions of people worldwide. Polymerase Chain Reaction (PCR) and real-time quantitative PCR (qPCR) have been used as tools to monitor parasitic levels in the bloodstream of individuals exposed to infection, thus enabling the monitoring of relapses and the effectiveness of therapy, for example. The aim of this study was to evaluate the TcSAT-IAM system, developed by our research group, on samples from patients with suspected Chagas disease infection. Initially, primer systems were developed for the detection of the nuclear DNA (SAT-DNA) from T. cruzi (TcSAT-IAM). The Cruzi system, predicted in the literature, and TcSAT-IAM were then evaluated in relation to their analytical sensitivity, specificity and efficiency. Afterwards, the applicability of the qPCR technique using both systems (separately) for the diagnosis of acute CD was evaluated in samples from 77 individuals exposed to the outbreak that occurred in Pernambuco-Brazil, relating the results obtained to those of the classical diagnostic methods recommended for this stage of the infection. TcSAT-IAM and Cruzi had a detection limit of 1 fg of target DNA (0,003 parasites). Thirty-eight cases were recorded, 28 by laboratory criteria and 10 by clinical and epidemiological criteria. Blood samples from 77 subjects were submitted to qPCR by both systems, reaching an agreement of 89.61% between them. After analyzes between systems and diagnostic criteria, the TcSAT-IAM showed sensitivity and specificity of 52.36% (CI 37.26–67.52) and 92.31% (CI 79.68–97.35), respectively, accuracy of 72.73% and moderate agreement. The TcSAT-IAM showed an accuracy of 72.58% and 75% in relation to parasitological and serological tests (IgM anti-T. cruzi), respectively. Therefore, quantitative PCR should be incorporated into the diagnosis of suspected acute cases of Chagas disease. [Display omitted] •QPCR as a diagnostic method for the detection of T. cruzi DNA in acute Chagas disease.•TcSAT-IAM proved to be applicable as a complementary technique for acute Chagas disease.•Samples targeted for qPCR should be collected prior to etiologic treatment.